Book Unbound: An exploration of the material forms of the codex and e-book. Issue 2 (1st December 2013) - Mak, Bonnie; Pollack, Julia
This article explores how material form influences the communication of information in books across technological divides. Using the creative project, Book Unbound, as a starting point, the article explores forms of the book that are not tied uniquely to the codex. Furthermore, by discussing the familiar codex in relation to its digital counterparts, the article examines how materiality continues to be used to communicate, persuade readers and shape the process of meaning-making.